Vasoactive-Inotropic Score and Vasoactive-Ventilation-Renal Score as Outcome Predictors for Children on Extracorporeal Membrane Oxygenation - Shukla, Ira; Hanson, Sheila J.; Yan, Ke; Zhang, Jian (Frontiers in Pediatrics, 2021)
We aimed to determine the association of Vasoactive-inotropic Score (VIS) and Vasoactive-Ventilation- Renal (VVR) score with in-hospital mortality and functional outcomes at discharge of children who receive ECMO. A sub-analysis of the multicenter, prospectively collected data by the Collaborative Pediatric Critical Care Research Network (CPCCRN) for Bleeding and Thrombosis on ECMO (BATE database) was conducted. Of the 514 patients who received ECMO across eight centers from December 2012 to February 2016, 421 were included in analysis. Patients > 18 years of age, patients placed on ECMO directly from cardiopulmonary bypass or as an exit procedure, or patients with an invalid or missing VIS score were excluded. Higher VIS (OR=1.008, 95% CI: 1.002-1.014, p=0.011) and VVR (OR: 1.006, 95% CI: 1.001-1.012, p=0.023) were associated with increased mortality. VIS was associated with worse Pediatric Cerebral Performance Category (PCPC) (OR=1.027, 95% CI: 1.010-1.044, p=0.002) and Pediatric Overall Performance Category (POPC) score (OR=1.023, 95% CI: 1.009-1.038, p=0.002) at discharge. No association was found between VIS or VVR and Functional Status Score (FSS) at discharge. Using multivariable analyses, controlling for ECMO mode, ECMO location, ECMO indication, primary diagnosis, and chronic diagnosis, extremely high VIS and VVR were still associated with increased mortality.